Staying focused when nobody is watching: Self‐regulatory strategies to reduce mind wandering during self‐directed learning. Issue 4 (5th January 2022) - Randall, Jason G.; Hanson, Matthew D.; Nassrelgrgawi, Alexander S.
Abstract: Mind wandering, the direction of attention away from a primary task, has the potential to interfere with learning, especially in increasingly common self‐directed learning environments. By integrating self‐regulated learning and mind wandering theories, we developed three interventions to encourage on‐task focus in a self‐directed training environment. We tested these self‐regulation interventions in two experiments: a field study with working adults (Study 1, N = 133) and a lab study with college students (Study 2, N = 175) where participants completed a self‐directed online Excel training. Overall, results from the two studies demonstrated that mind wandering negatively harms self‐directed training outcomes, including knowledge, self‐efficacy, and trainee reactions. The strength of these effects differed between samples, with mind wandering more harmful in Study 2 where the participants were significantly less motivated. There was little evidence that the self‐regulation interventions significantly influenced mind wandering or training outcomes when compared to a control group. However, correlational results suggest possible deterrents of mind wandering, including mindfulness, metacognitive monitoring, implementation intentions, and environmental structuring. Drawing from our multidisciplinary theoretical integration and the empirical results presented here, we provide recommendations for future theoretical development and applied research to reduce off‐task thought and enhance performance in self‐directed training.